Preliminary Investigation of Urban Quality of Life: Towards Effective Measurements of Wellbeing in New Urban Communities in Cairo. - Elnady, Aly (AUC Knowledge Fountain, 2024)
This study focuses on investigating Urban Quality of Life (UQoL) in New Cairo as a case study for New Urban Communities (NUCs) in the Greater Cairo Region. The objective of this thesis is to get an accurate description of urban life in NUCs as a distinct mode of urbanization. The study investigates residents’ Subjective Well Being (SWB) and life satisfaction within a wide range of urban life domains, grouped in a conceptual framework of seven sections: Housing & Neighbourhood Quality, Transport & Mobility, Health & Wellness, Education & Employment, Culture & Recreation, Social & Community Support, and Governance & Neighbourhood Management. The research follows a qualitative approach to capture residents’ perceptions on the suitability and availability of hard infrastructure, certain amenities and services, and the relational quality between the built environment and residents. The study applies two research methods, face to face interviews with residents, urban studies academics, and one policymaker, and a Likert based survey for residents (which garnered 75 responses). Overall, in testing the survey’s universality and effectiveness in capturing UQoL, survey results showed that residents are ‘unsatisfied’ with Urban Quality of Life in New Cairo. This was further corroborated through face-to-face interviews where several interrelated themes emerged regarding expectations and realities of migrating to New Cairo, movement and accessibility, social disintegration, and the divergent nature of how NUCs are perceived by urban experts and government officials.